Ouabain at nanomolar concentrations is cytotoxic for biliary tract cancer cells. - Christian Mayr; Tobias Kiesslich; Dino Bekric; Marlena Beyreis; Michael Kittl; Celina Ablinger; Elen Neureiter; Martin Pichler; Felix Prinz; Markus Ritter; Daniel Neureiter; Martin Jakab; et al. (PLoS ONE, 2023)
Biliary tract cancer is a deadly disease with limited therapeutic options. Ouabain is a well-known inhibitor of the pumping function of Na+/K+-ATPase, though there is evidence that low concentrations of ouabain lead to a reduction of cell viability of cancer cells independent of its inhibition of the pumping function of the Na+/K+-ATPase. Regarding the impact of ouabain on biliary tract cancer, no data is currently available. Therefore, we aimed for a first-time investigation of ouabain as a potential anti-neoplastic biliary tract cancer agent using comprehensive human biliary tract cancer in vitro models. We found that ouabain has a strong cell line-dependent cytotoxic effect with IC50 levels in the (low) nanomolar-range and that this effect was not associated with the mRNA expression levels of the Na+/K+-ATPase α, β and fxyd-subunits. Regarding the mode of cytotoxicity, we observed induction of apoptosis in biliary tract cancer cells upon treatment with ouabain. Interestingly, cytotoxic effects of ouabain at sub-saturating (< μM) levels were independent of cellular membrane depolarization and changes in intracellular sodium levels. Furthermore, using a 3D cell culture model, we found that ouabain disturbs spheroid growth and reduces the viability of biliary tract cancer cells within the tumor spheroids. In summary, our data suggest that ouabain possesses anti-biliary tract cancer potential at low μM-concentration in 2D and 3D in vitro biliary tract cancer models and encourage further detailed investigation.